Clinical profile of women seeking medical termination of pregnancy at a tertiary care institute, South India - Aggrawal, Pratima; Dasari, Papa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Medical termination of pregnancy (MTP) has largely become a medical procedure rather than surgical and in the recent times and few women approach public health care facility and hence the profile of women has changed and is different in various hospitals. Hence this study was undertaken with the objectives to know the proportion of indications as per MTP act and gestational age in women who opted MTP. The study also aimed to find out the clinic-demographic profile and the method of MTP and contraception adopted along with MTP. Methods: A retrospective cohort over 3 year period (2016-2019). Data was extracted from the medical records of women who were hospitalised for MTP and analysed for the outcome parameters Viz: Women were categorised as per the indication for MTP. In each category of indication, age, socioeconomic status, trimester of MTP, number of living children, methods of MTP and methods of contraception adopted was noted. The results were expressed as proportions and frequencies and the trend over 3 years was expressed as percentage per total number of deliveries per year. Results: There were 640 MTPs over 3 year period and this constituted 1.22% of total deliveries (52,555). Fifty one percent were first trimester MTPs. Thirty eight percent were done for congenital malformations, 32% for socio-economic reasons of family limitation, 17% for saving physical or mental health , 4% for rape victims and 8% for failure of contraception. The mean age was 28 years and the age in humanitarian group was ≤ 20 years. More than 88% belonged to lower socioeconomic class and 37% were third gravidae with 2 living children. Medical methods were used in 90% of terminations and 46% adopted contraception. Conclusions: The most common reason for opting MTP is congenital malformation of fetus. Women who achieved the desired family size and non-practice of contraception was the next common indication for termination of pregnancy and majority of terminations in this group were first trimester. Practice of contraception to avoid unwanted pregnancy and measures to prevent congenital malformations are essential to reduce medical termination of pregnancies.